(untitled) (Asian Journal of Social Science Studies, 2021)
Second-wave feminism was a period of feminist activity that began in the early 1960s in the western world, which focused on criticizing the patriarchal institutions or cultural practices throughout the society. Originating several centuries earlier, Chinese opera culture has been ahead of its time in demonstrating the male-dominated society’s oppression against women. As one of the principal founders of second-wave feminism, Simone de Beauvoir’s classical feminist theory in her book, The Second Sex, mainly introduced the sex-gender distinction. In this article, the author aims to reveal how Bi Feiyu, the writer of The Moon Opera, successfully conveyed existential feminist ideas, especially Beauvoir’s famous assertion that "one is not born but becomes a woman", through his careful selection of the art type Qing Yi (Qingyi is the main woman role in Peking Opera and often plays dignified, serious, and decent characters, which are mostly wives or mothers undergoing severe ordeal) and the portrayal of two generations of Qing Yi performers. In the process of analysis, the author not only examined Bi Feiyu’s application of intertextuality theory, but also derived conclusions from other mainstream feminist thoughts such as the feminist theory of the dressed female body and the transactional sex theory.